Digital Transformation of Public Asset Management via Web-Based Lifecycle System for Diskominfo Kota Bandung - Jasman Pardede; Noval Rizky Nugraha; Muhammad Zaki Mahran Mufid; Muhammad Mulyawan (Universitas Serang Raya, 2026)
Public asset management at Diskominfo Kota Bandung faces challenges related to manual administrative procedures, including data inconsistencies and difficulties in asset tracking. This community service activity aimed to introduce a prototype of the